Predictive thermal inactivation model of salmonella typhimurium in citrus systems - Gabriel, Alonzo Alulod (2007)
A highly significant (P<0.0001) predictive model for the decimal reduction times (D72°C) of Salmonella Typhimurium (ATCC 13311) as a function of pH, tillable acidity and soluble solids of citrus model systems was developed. The model exhibited acceptable predictive mathematical accuracy and bias; and resulted in fail-safe predictions, when validated in some natural citrus and non-citrus juices. The model was also found to be applicable in predicting the D72°C of other reference strain in a citrus juice drink medium but was found to result in fail-dangerous predictions in fruit juices that contain significant amounts of suspended pulps. A model-based pasteurization process that resulted in an acceptable orange juice drink validated the utility of the model in establishing thermal processes for appropriate fruit systems